Sulfide solid electrolyte membrane, method for manufacturing the same, battery, and power using device

CN122950585APending Publication Date: 2026-10-20BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610083601.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-21
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

1.空气稳定性差:硫化物电解质对水分极为敏感,暴露于空气中易发生水解反应,产生剧毒、腐蚀性的硫化氢气体,并导致材料结构破坏、离子电导率急剧下降

Benefits of technology

通过在硫化物固态电解质膜中同时掺杂硼元素(B)和氮元素(N),可使硫化物固态电解质膜兼具优异的空气稳定性、离子电导率和电化学界面稳定性,提升电池的循环寿命等电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_78
    Figure SMS_78
Patent Text Reader

Abstract

This application discloses a sulfide solid electrolyte membrane, its preparation method, battery, and electrical device. The preparation method of the sulfide solid electrolyte membrane includes: mixing a solid component and a solvent, forming a film, to obtain the sulfide solid electrolyte membrane; the solid component includes an additive, which includes ammonium borate. The sulfide solid electrolyte membrane prepared by the method of this application has high ionic conductivity and excellent air stability, which can significantly improve the stability of the negative electrode interface, reduce side reactions and lithium dendrite growth, and achieve a longer cycle life. In addition, the process is simple, requires no expensive equipment or extreme conditions, has high compatibility with existing battery slurry coating production lines, and the additive ammonium borate is inexpensive, making it highly potential for large-scale industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery materials technology, and in particular to a sulfide solid electrolyte membrane and its preparation method, battery and power device. Background Technology

[0002] Sulfide solid electrolyte membranes are characterized by their extremely high lithium-ion conductivity (up to 100%). (On a scale of 1000-2000 liters) is considered one of the core materials for all-solid-state batteries. However, it still faces several key bottlenecks in its industrial application: 1. Poor air stability: Sulfide electrolytes are extremely sensitive to moisture. Exposure to air easily leads to hydrolysis, producing highly toxic and corrosive hydrogen sulfide gas, causing structural damage and a sharp decrease in ionic conductivity. This imposes extremely stringent requirements on their production, storage, and battery assembly environments (e.g., dew point). The requirements significantly increase costs.

[0003] 2. Insufficient electrochemical interface stability: Especially when in contact with a strongly reducing negative electrode, the sulfide electrolyte is easily reduced, forming an unstable, high-resistivity interface layer, which leads to a decline in battery cycle performance and the risk of lithium dendrite growth.

[0004] To improve the aforementioned performance, related technologies typically employ elemental doping strategies. For example, some technologies use high-temperature solid-state sintering for doping, specifically by introducing a dopant source (such as...) during the synthesis of sulfide electrolyte powders. Some methods involve co-firing the dopant with the raw materials at high temperatures. However, this method is complex, energy-intensive, and the dopant elements may be unevenly distributed, easily introducing impurity phases. Other technologies use mechanical ball milling to mix the dopant and electrolyte powder. While simple, this method only physically adheres the dopant to the particle surface, making it difficult to achieve effective doping at the atomic scale, resulting in limited modification effects and potential impact on ion conduction pathways. Still other technologies employ single-element doping, with most studies focusing on doping with a single element (such as O, Si, Ge, Sn, etc.). Although this can improve certain aspects (such as stability or conductivity), it often fails to address the multiple challenges of air stability, ionic conductivity, and interface stability in a synergistic manner.

[0005] In summary, there is an urgent need for a sulfide solid electrolyte membrane that possesses at least the following advantages: good air stability, high electrochemical interface stability, and simple and low-cost preparation process. Summary of the Invention

[0006] In view of this, one object of this application is to provide a sulfide solid electrolyte membrane, which, by simultaneously doping boron (B) and nitrogen (N) into the sulfide solid electrolyte membrane, can possess excellent air stability, ionic conductivity and electrochemical interface stability, thereby improving the electrochemical performance of the battery, such as cycle life.

[0007] Another objective of this application is to provide a method for preparing a sulfide solid electrolyte membrane.

[0008] Another object of this application is to provide a battery.

[0009] Another object of this application is to provide an electrical device.

[0010] To achieve the above objectives, the first aspect of this application proposes a sulfide solid electrolyte membrane, wherein the sulfide solid electrolyte membrane is doped with boron and nitrogen.

[0011] The sulfide solid electrolyte membrane of this application can bring at least the following beneficial effects: By simultaneously doping boron (B) and nitrogen (N) into a sulfide solid electrolyte membrane, the sulfide solid electrolyte membrane can possess excellent air stability, ionic conductivity, and electrochemical interface stability, thereby improving the battery's cycle life and other electrochemical performance.

[0012] In some embodiments, the boron element in the sulfide solid electrolyte membrane has a mass content of 0.02-1%.

[0013] In some embodiments, the N element in the sulfide solid electrolyte membrane has a mass content of 0.002-0.4%.

[0014] In some embodiments, the raw materials for preparing the sulfide solid electrolyte membrane include solid components and solvents, wherein the solid components include sulfide solid electrolytes, additives and binders, and the additives include ammonium borate.

[0015] In some embodiments, the ammonium borate includes at least one of ammonium tetraborate, ammonium metaborate, and ammonium orthoborate.

[0016] In some embodiments, the ammonium borate content in the solid component is 0.1-5% by mass.

[0017] In some embodiments, the sulfide solid electrolyte includes at least one of sulfide solid electrolyte of the silver-germanium sulfide type, LGPS type sulfide solid electrolyte, and thiolated LISICON type solid electrolyte.

[0018] In some embodiments, the sulfide solid electrolyte has a mass content of 85-99.4% in the solid component.

[0019] In some embodiments, the adhesive includes at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyurethane (PU), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), and hydrogenated styrene-butadiene block copolymer (SEBS).

[0020] In some embodiments, the binder has a mass content of 0.5-10% in the solid component.

[0021] In some embodiments, the solid component has a mass content of 10-90% in the raw materials used for preparation.

[0022] In some embodiments, the solvent includes at least one of toluene, xylene, butyl butyrate, isobutyl isobutyrate, anisole, or hexane.

[0023] The second aspect of this application discloses a method for preparing a sulfide solid electrolyte membrane, comprising: The solid components and solvent are mixed and formed into a film to obtain the sulfide solid electrolyte membrane; The solid component includes additives, including ammonium borate.

[0024] The method for preparing the sulfide solid electrolyte membrane of this application can bring at least the following beneficial effects: (1) Excellent air stability: The prepared B and N co-doped sulfide solid electrolyte membrane exhibits a significant decrease in ionic conductivity after being exposed for the same period of time in a low dew point dry room (e.g., -20°C dew point). This greatly relaxes the requirements for the production environment.

[0025] (2) Maintaining high ionic conductivity: Due to the mild and uniform in-situ doping reaction, the main lithium-ion transport channels are not severely disrupted. The total ionic conductivity of the prepared sulfide solid electrolyte membrane can be maintained at room temperature. The apparent conductivity is comparable to that of undoped high-quality electrolytes, and some implementations even exhibit higher apparent conductivity due to interface optimization.

[0026] (3) Improve cycle life: The prepared sulfide solid electrolyte membrane can significantly improve the stability of the negative electrode interface, reduce side reactions and lithium dendrite growth, and achieve a longer cycle life.

[0027] (4) Technological and economic advantages: The preparation method is simple, does not require expensive equipment or extreme conditions, is highly compatible with existing battery slurry coating production lines, and the additive ammonium borate is inexpensive, making it highly promising for large-scale industrial application.

[0028] In some embodiments, the ammonium borate includes at least one of ammonium tetraborate, ammonium metaborate, and ammonium orthoborate.

[0029] In some embodiments, the ammonium borate content in the solid component is 0.1-5% by mass.

[0030] In some embodiments, the solid component further includes a sulfide solid electrolyte and a binder.

[0031] In some embodiments, the sulfide solid electrolyte includes at least one of sulfide solid electrolyte of the silver-germanium sulfide type, LGPS type sulfide solid electrolyte, and thiolated LISICON type solid electrolyte.

[0032] In some embodiments, the sulfide solid electrolyte has a mass content of 85-99.4% in the solid component.

[0033] In some embodiments, the adhesive includes at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyurethane (PU), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), and hydrogenated styrene-butadiene block copolymer (SEBS).

[0034] In some embodiments, the binder has a mass content of 0.5-10% in the solid component.

[0035] In some embodiments, the mass content of the solid component is 10-90% based on the total mass of the solid component and the solvent.

[0036] In some embodiments, the solvent includes at least one of toluene, xylene, butyl butyrate, isobutyl isobutyrate, anisole, or hexane.

[0037] In some embodiments, the mixing is carried out in an inert gas atmosphere or a drying room.

[0038] In some embodiments, the mixing method includes at least one of stirring, ball milling, and high-speed shearing; the high-speed shearing speed is 1000-100000 rpm.

[0039] In some embodiments, the mixing temperature is 0-60°C, and the mixing time is 10 min to 24 h.

[0040] In some embodiments, the film formation includes: The slurry obtained by mixing is formed on a substrate to obtain a wet film; The wet film is dried in an inert gas atmosphere or a vacuum environment.

[0041] The third aspect of this application discloses a battery comprising a positive electrode, a negative electrode, and a solid electrolyte membrane, wherein the solid electrolyte membrane comprises the sulfide solid electrolyte membrane described in the first aspect of this application, or a sulfide solid electrolyte membrane prepared by the method described in the second aspect of this application.

[0042] In some embodiments, the battery includes an all-solid-state battery.

[0043] The fourth aspect of this application provides an electrical device including the battery described in the third aspect of this application.

[0044] In some embodiments, the electrical device includes one of a vehicle, a lighting device, or an electronic device.

[0045] The batteries and electrical devices described in this application have at least the beneficial effects of the sulfide solid electrolyte membrane and the method for preparing the sulfide solid electrolyte membrane described in this application.

[0046] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0047] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the following description of the embodiments taken in conjunction with the accompanying drawings. in: Figure 1 The battery cycle curves are for an all-solid-state lithium-ion secondary battery containing the sulfide solid electrolyte membrane prepared in Example 2. Detailed Implementation

[0048] The embodiments of this application are described in detail below. These embodiments are exemplary and intended to explain this application, and should not be construed as limiting this application.

[0049] In this application, the disclosure of numerical ranges includes all values ​​throughout the range and the disclosure of further subdivisions of the range, including the endpoints and subranges given for these ranges.

[0050] Unless otherwise specified, all raw materials and equipment involved in this application are self-made through commercial means or known methods; and all methods involved are conventional methods unless otherwise specified.

[0051] When the term “and / or” is used in a list containing two or more items, it means that any of the listed items can be used alone or in combination with any one or more of the listed items. For example, the expression “A and / or B” is intended to mean A or B or A and B, that is, A only, B only, or a combination of A and B.

[0052] In this application, room temperature refers to 20-30°C.

[0053] In this application, air stability refers to the change in ionic conductivity in exposed air, and improving air stability enhances the retention rate of ionic conductivity.

[0054] The inventors discovered that existing sulfide solid electrolyte membranes suffer from key bottlenecks in industrial applications, such as poor air stability and insufficient electrochemical interface stability. Related technologies employing element doping strategies—high-temperature solid-state sintering, mechanical ball milling, and single-element doping—still cannot simultaneously overcome these defects and may also suffer from problems such as complex processes, high energy consumption, and low ionic conductivity.

[0055] Based on the above findings, the inventor accidentally discovered the following two points: First, by simultaneously doping boron and nitrogen elements into the sulfide solid electrolyte membrane, the sulfide solid electrolyte membrane can possess both excellent air stability and electrochemical interface stability.

[0056] Second, if ammonium borate containing boron and nitrogen is used as an additive, and it undergoes a spontaneous chemical reaction with the surface or near-surface of sulfide solid electrolyte particles during the preparation of a slurry containing solvent, in-situ synergistic doping of boron and nitrogen into the sulfide solid electrolyte film can be achieved. Specifically: (1) Selection of additives and doping mechanism: Ammonium borate was selected as the sole or key additive. Ammonium borate is an inexpensive and readily available chemical raw material. It provides both boron (B) and nitrogen (N) sources in a single molecule. During slurry mixing, it can spontaneously and in situ react with the sulfide solid electrolyte to achieve co-doping of B and N in one step. This eliminates the complex process of introducing B and N sources separately in the traditional method, and achieves efficient and low-cost dual-element modification.

[0057] (2) In-situ reaction doping method based on slurry process: Doping is achieved through the chemical reaction between ammonium borate and sulfide solid electrolyte during the slurry preparation stage (wet mixing process in the presence of solvent). This method has the following advantages: 1) Simple process: No additional high-temperature sintering or complex post-processing steps are required. It is perfectly compatible with conventional solution film-forming processes and is easy to scale up. 2) Uniform doping: The reaction occurs in the liquid phase slurry system, which can achieve uniform modification at the molecular / atomic level on the surface of sulfide solid electrolyte particles, avoiding the inhomogeneity of physical mixing and the local over-reaction of high-temperature sintering. 3) Mild and controllable reaction: The reaction in the slurry environment is milder than solid-phase sintering, which is conducive to controlling the reaction depth and avoiding damage to the main structure of the electrolyte.

[0058] (3) Synergistic enhancement effect of B and N elements: By selecting ammonium borate as an additive, the synergistic co-doping of boron and nitrogen can be achieved based on the "in-situ reaction doping" method of slurry process. Its advantages and mechanism are as follows: The role of boron (B): The B atom has a chalcophilic nature and tends to form strong covalent bonds with S. This bonding stabilizes the sulfide lattice, anchors sulfur atoms on the surface, and significantly reduces their reactivity with water molecules, thereby greatly improving the air stability of the electrolyte membrane. Simultaneously, appropriate boron doping may optimize… The transmission channel maintains or even slightly enhances ionic conductivity.

[0059] The role of nitrogen (N): The introduction of nitrogen may form or Nitrogen-containing interface layers. These nitrogen-containing components possess high lithium-ion conductivity and good electronic insulation, as well as good thermodynamic reduction stability. When in contact with a strongly reducing negative electrode, they can induce the formation of a dense, stable, and highly ionicly conductive solid electrolyte interface (SEI), effectively reducing interfacial impedance and suppressing side reactions and lithium dendrite growth.

[0060] Synergistic Effect: Co-doping of boron (B) and nitrogen (N) is not a simple additive process. B enhances the intrinsic stability of the bulk phase and surface, while N optimizes interfacial dynamics. Together, they provide dual protection from the bulk phase to the interface, resulting in a synergistic effect. The synergistic enhancement effect of "".

[0061] Based on the above findings, embodiments of this application propose sulfide solid electrolyte membranes, their preparation methods, and applications.

[0062] The following details the sulfide solid electrolyte membrane and its preparation method according to embodiments of this application.

[0063] <Sulfide Solid Electrolyte Membrane> The sulfide solid electrolyte membrane of this application embodiment is doped with boron and nitrogen.

[0064] The sulfide solid electrolyte membrane of this application, by simultaneously doping boron (B) and nitrogen (N) into the sulfide solid electrolyte membrane, can have excellent air stability, ionic conductivity and electrochemical interface stability, thereby improving the electrochemical performance of the battery, such as cycle life.

[0065] Specifically: The role of boron (B): B atoms are chalcophilic and tend to form strong covalent bonds (BS) with sulfur. This bonding stabilizes the sulfide lattice, anchors sulfur atoms on the surface, and significantly reduces their reactivity with water molecules, thereby greatly improving the air stability of the electrolyte membrane. Furthermore, appropriate B doping may optimize… The transmission channel maintains or even slightly enhances ionic conductivity.

[0066] The role of nitrogen (N): The introduction of nitrogen may form or Nitrogen-containing interface layers. These nitrogen-containing components possess high lithium-ion conductivity and good electronic insulation, as well as good thermodynamic reduction stability. When in contact with a strongly reducing negative electrode, they can induce the formation of a dense, stable, and highly ionicly conductive solid electrolyte interface (SEI), effectively reducing interfacial impedance and suppressing side reactions and lithium dendrite growth.

[0067] Synergistic effect of boron (B) and nitrogen (N): Co-doping of B and N is not a simple additive process. B enhances the intrinsic stability of the bulk phase and surface, while N optimizes interfacial dynamics. Together, they create a dual protection from the bulk phase to the interface, resulting in a synergistic effect. The synergistic enhancement effect of "".

[0068] In some embodiments, the boron element in the sulfide solid electrolyte membrane has a mass content of 0.02-1%, including but not limited to 0.03%, 0.05%, 0.1%, 0.15%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 0.95%.

[0069] In some embodiments, the nitrogen element in the sulfide solid electrolyte membrane has a mass content of 0.002-0.4%, including but not limited to 0.003%, 0.005%, 0.07%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3%, 0.32%, 0.35%, or 0.38%.

[0070] In the embodiments of this application, controlling the boron and nitrogen elements in the sulfide solid electrolyte membrane to be within the above-mentioned ranges can better realize the effects of boron (B), nitrogen (N), and their synergistic effect, ensuring that the sulfide solid electrolyte membrane has better air stability, ionic conductivity, and electrochemical interface stability.

[0071] In some embodiments, the raw materials for preparing the sulfide solid electrolyte membrane include solid components and solvents, wherein the solid components include sulfide solid electrolytes, additives and binders, and the additives include ammonium borate.

[0072] In the embodiments of this application, ammonium borate, an additive, is an inexpensive and readily available chemical raw material. It simultaneously provides both boron (B) and nitrogen (N) sources within a single molecule. During slurry mixing, it spontaneously and in situ reacts with the sulfide solid electrolyte, achieving co-doping of B and N in a single step. This eliminates the complex process of separately introducing B and N sources, achieving efficient and low-cost bi-element modification.

[0073] In some embodiments, the ammonium borate includes, but is not limited to, ammonium tetraborate ( ), ammonium metaborate ( ), ammonium borate ( At least one of the following: ammonium borate, etc. By selecting these types, dual doping with boron and nitrogen can be achieved; furthermore, these substances have high nitrogen and boron content, allowing for good improvement even with small amounts of doping.

[0074] In some embodiments, the ammonium borate content in the solid component is 0.1-5% by mass, including but not limited to 0.25%, 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, 2%, 2.25%, 2.5%, 2.75%, 3%, 3.25%, 3.5%, 3.75%, 4%, 4.25%, 4.5%, or 4.75%.

[0075] In the embodiments of this application, controlling the mass content of ammonium borate in the solid component within the above-mentioned range can not only improve the air stability and electrochemical stability of the sulfide solid electrolyte membrane, but also ensure that doping within this range does not affect the structure of the sulfide solid electrolyte body, thus preventing a decrease in the initial conductivity of the sulfide solid electrolyte membrane. If the content is below 0.1%, effective boron and nitrogen doping may not be formed, which may prevent the effective improvement of the air stability and electrochemical stability of the electrolyte membrane. If the content is above 5%, the structure of the sulfide solid electrolyte body may be affected, which may in turn affect the lithium-ion conduction ability of the sulfide solid electrolyte, resulting in a significant decrease in the conductivity of the sulfide solid electrolyte membrane.

[0076] As an alternative example, the additive is ammonium borate.

[0077] It should be noted that the specific selection of the sulfide solid electrolyte in the embodiments of this application is not limited, and it can be any sulfide solid electrolyte well known in the art for use in batteries, especially all-solid-state secondary batteries.

[0078] As an optional example, the sulfide solid electrolyte includes, but is not limited to, at least one of the following: argyrodite-type sulfide solid electrolyte, LGPS-type sulfide solid electrolyte, and Thio-LISICON-type sulfide solid electrolyte.

[0079] For example, the sulfide solid electrolyte of the silver-germanium sulfide type includes, but is not limited to, those containing, silver-germanium sulfide. At least one of the following.

[0080] For example, the LGPS type sulfide solid electrolyte includes, but is not limited to, […]. At least one of the following. Among them, The values ​​of y include, but are not limited to, 0.1, 0.3, 0.5, 0.7, 0.9, 1, 1.2, 1.4, 1.6, or 1.8.

[0081] For example, the thiolated LISICON-type solid electrolyte includes, but is not limited to, the following: Solid solutions (e.g., wait), Solid solutions (e.g., wait), Solid solutions (e.g., wait), ( ) 、 ​ At least one of the following.

[0082] In some embodiments, the sulfide solid electrolyte has a mass content of 85-99.4% in the solid component, including but not limited to 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 95%, 95%, 96%, 97%, 98%, or 99%.

[0083] In the embodiments of this application, by controlling the mass content of the sulfide solid electrolyte in the solid component within the above-mentioned range, the excellent lithium-ion transport capability of the sulfide solid electrolyte membrane can be achieved, giving it high ionic conductivity while maintaining good mechanical properties to meet the requirements of subsequent processing.

[0084] In some embodiments, the sulfide solid electrolyte is a sulfide solid electrolyte powder.

[0085] Adding a binder to the raw materials for preparing sulfide solid electrolyte membranes can improve mechanical support and film-forming properties, giving the sulfide solid electrolyte membranes a good ion conduction network, a stable electrode / electrolyte interface, and good processability.

[0086] In some embodiments, the adhesive includes, but is not limited to, at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyurethane (PU), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), and hydrogenated styrene-butadiene block copolymer (SEBS).

[0087] In some embodiments, the binder has a mass content of 0.5-10% in the solid component, including but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%.

[0088] In the embodiments of this application, the binder is selected from the above-mentioned substances and / or its content is controlled within the above-mentioned range, which can better achieve the following effects: improve mechanical support and film-forming properties, so that the sulfide solid electrolyte membrane has a good ion conduction network, a stable electrode / electrolyte interface and good processability.

[0089] As an alternative example, the solid component consists of the sulfide solid electrolyte, the additive, and the binder.

[0090] In some embodiments, the solid component in the preparation raw material has a mass content of 10-90%, including but not limited to 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%, etc.

[0091] In the embodiments of this application, adding a solvent to the raw materials facilitates doping through the chemical reaction between ammonium borate and sulfide solid electrolyte during the raw material slurry preparation stage (wet mixing process in the presence of solvent).

[0092] In some embodiments, the solvent includes, but is not limited to, at least one of toluene, xylene, butyl butyrate, isobutyl isobutyrate, anisole, or hexane. Such substances, as solvents, exhibit good stability to the sulfide solid electrolyte and do not participate in the reaction between ammonium borate and the sulfide solid electrolyte.

[0093] In some embodiments, the thickness of the sulfide solid electrolyte membrane is 20-100µm, including but not limited to 30µm, 40µm, 50µm, 60µm, 70µm, 80µm or 90µm.

[0094] <Preparation Method of Sulfide Solid Electrolyte Membrane> The method for preparing the sulfide solid electrolyte membrane according to the embodiments of this application can be used to prepare the sulfide solid electrolyte membrane according to the embodiments of this application. The core objective of this method is: 1. A simple and low-cost slurry process is used to achieve effective elemental doping of sulfide solid electrolytes during film formation.

[0095] 2. Achieve synergistic co-doping of boron (B) and nitrogen (N) to simultaneously improve the air stability of the sulfide solid electrolyte membrane and the interfacial stability to the negative electrode.

[0096] 3. Ensure that the dopant elements can chemically react with the electrolyte matrix to achieve atomic-level bonding, rather than simple physical mixing, thereby obtaining a lasting and uniform modification effect.

[0097] The method for preparing the sulfide solid electrolyte membrane according to the embodiments of this application includes the following steps: The solid components and solvent are mixed and formed into a film to obtain the sulfide solid electrolyte membrane; the solid components include additives, including ammonium borate.

[0098] In some embodiments, the solid component further includes a sulfide solid electrolyte and a binder.

[0099] In the embodiments of this application, during the mixing of the solid components and solvent, ammonium borate spontaneously reacts with the surface or near-surface of the sulfide solid electrolyte particles. A possible reaction mechanism is that, under the influence of solvent and mechanical energy, ammonium ions and borate ions in the ammonium borate react with those in the electrolyte... When ion exchange or reaction occurs, it produces a product containing... The surface layer is so homogeneous that boron (B) and nitrogen (N) elements are introduced in situ into the lattice of the sulfide electrolyte or into the strongly chemically bonded surface modification layer, thereby achieving B and N co-doping.

[0100] In some embodiments, the ammonium borate includes, but is not limited to, ammonium tetraborate ( ), ammonium metaborate ( ), ammonium borate ( At least one of the following: ammonium borate, etc. By selecting these types, dual doping with boron and nitrogen can be achieved; furthermore, these substances have high nitrogen and boron content, allowing for good improvement even with small amounts of doping.

[0101] In some embodiments, the ammonium borate content in the solid component is 0.1-5% by mass, including but not limited to 0.25%, 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, 2%, 2.25%, 2.5%, 2.75%, 3%, 3.25%, 3.5%, 3.75%, 4%, 4.25%, 4.5%, or 4.75%.

[0102] In the embodiments of this application, controlling the mass content of ammonium borate in the solid component within the above-mentioned range can not only improve the air stability and electrochemical stability of the sulfide solid electrolyte membrane, but also ensure that doping within this range does not affect the structure of the sulfide solid electrolyte body, thus preventing a decrease in the initial conductivity of the sulfide solid electrolyte membrane. If the content is below 0.1%, effective boron and nitrogen doping may not be formed, which may prevent the air stability and electrochemical stability of the sulfide solid electrolyte membrane from being effectively improved. If the content is above 5%, the structure of the sulfide solid electrolyte body may be affected, which may in turn affect the electrolyte's ability to conduct lithium ions, resulting in a significant decrease in the conductivity of the sulfide solid electrolyte membrane.

[0103] As an alternative example, the additive is ammonium borate.

[0104] It should be noted that the specific selection of the sulfide solid electrolyte in the embodiments of this application is not limited, and it can be any sulfide solid electrolyte well known in the art for use in batteries, especially all-solid-state secondary batteries.

[0105] As an optional example, the sulfide solid electrolyte includes, but is not limited to, at least one of the following: argyrodite-type sulfide solid electrolyte, LGPS-type sulfide solid electrolyte, and Thio-LISICON-type sulfide solid electrolyte. By selecting these sulfide solid electrolytes, sulfide solid electrolyte membranes with high ionic conductivity can be prepared.

[0106] For example, the sulfide solid electrolyte of the silver-germanium sulfide type includes, but is not limited to, those containing, silver-germanium sulfide. At least one of the following.

[0107] For example, the LGPS type sulfide solid electrolyte includes, but is not limited to, […]. At least one of the following. Among them, The values ​​of y include, but are not limited to, 0.1, 0.3, 0.5, 0.7, 0.9, 1, 1.2, 1.4, 1.6, or 1.8.

[0108] For example, the thiolated LISICON-type solid electrolyte includes, but is not limited to, the following: Solid solutions (e.g., wait), Solid solutions (e.g., wait), Solid solutions (e.g., wait), ( ) 、 ​ At least one of the following.

[0109] In some embodiments, the sulfide solid electrolyte has a mass content of 85-99.4% in the solid component, including but not limited to 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 95%, 95%, 96%, 97%, 98%, or 99%.

[0110] In the embodiments of this application, by controlling the mass content of the sulfide solid electrolyte in the solid component within the above-mentioned range, the excellent lithium-ion transport capability of the sulfide solid electrolyte membrane can be achieved, giving it high ionic conductivity while maintaining good mechanical properties to meet the requirements of subsequent processing.

[0111] In some embodiments, the sulfide solid electrolyte is a sulfide solid electrolyte powder.

[0112] In the embodiments of this application, the binder can improve mechanical support and film-forming properties, enabling the sulfide solid electrolyte membrane to have a good ion conduction network, a stable electrode / electrolyte interface, and good processability.

[0113] In some embodiments, the adhesive includes, but is not limited to, at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyurethane (PU), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), and hydrogenated styrene-butadiene block copolymer (SEBS).

[0114] In some embodiments, the binder has a mass content of 0.5-10% in the solid component, including but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%.

[0115] In the embodiments of this application, the binder is selected from the above-mentioned substances and / or its content is controlled within the above-mentioned range, which can better achieve the following effects: improve mechanical support and film-forming properties, so that the sulfide solid electrolyte membrane has a good ion conduction network, a stable electrode / electrolyte interface and good processability.

[0116] As an alternative example, the solid component consists of the sulfide solid electrolyte, the additive, and the binder.

[0117] In some embodiments, the mass content of the solid component is 10-90% based on the total mass of the solid component and the solvent, including but not limited to 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or 85%.

[0118] In the embodiments of this application, the presence of solvent is beneficial for doping to be achieved through the chemical reaction between ammonium borate and sulfide solid electrolyte during the raw material slurry preparation stage (wet mixing process in the presence of solvent).

[0119] In some embodiments, the solvent includes, but is not limited to, at least one of toluene, xylene, butyl butyrate, isobutyl isobutyrate, anisole, or hexane. Such substances, as solvents, exhibit good stability to the sulfide solid electrolyte and do not participate in the reaction between ammonium borate and the sulfide solid electrolyte.

[0120] In some embodiments, the mixing is carried out in an inert gas atmosphere or a drying room.

[0121] For example, during the mixing process, the inert gas includes, but is not limited to, at least one of helium, argon, and neon, and may be selected as argon.

[0122] For example, the dew point of the drying room is below -40°C, including but not limited to below -45°C, below -50°C, below -55°C, below -60°C, or below -70°C, and can be selected as -40°C to -70°C.

[0123] In some embodiments, the mixing method includes, but is not limited to, at least one of stirring, ball milling, high-speed shearing, etc.

[0124] For example, the stirring speed is 10-500 rpm, including but not limited to 50 rpm, 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm or 450 rpm.

[0125] For example, the ball milling speed is 10-500 rpm, including but not limited to 50 rpm, 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm or 450 rpm.

[0126] For example, the high-speed shearing speed is 1000-100000 rpm, including but not limited to 5000 rpm, 10000 rpm, 20000 rpm, 30000 rpm, 40000 rpm, 50000 rpm, 60000 rpm, 70000 rpm, 80000 rpm, 90000 rpm, or 100000 rpm.

[0127] In the embodiments of this application, mixing is carried out by means of stirring, ball milling, high-speed shearing, etc., and their respective speeds are controlled within the above-mentioned range, so as to achieve uniform dispersion of sulfide solid electrolyte slurry.

[0128] In some embodiments, the mixing temperature is 0-60°C, including but not limited to 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, or 55°C.

[0129] In some embodiments, the mixing time is from 10 min to 24 h, including but not limited to 1 h, 2 h, 3 h, 4 h, 5 h, 7 h, 9 h, 11 h, 13 h, 15 h, 17 h, 19 h, 21 h or 23 h, and can be selected as 0.5-5 h.

[0130] In the embodiments of this application, by controlling the mixing temperature and time within the above-mentioned ranges, a good dispersion effect can be achieved without damaging the structure of the sulfide solid electrolyte.

[0131] It should be noted that, in the embodiments of this application, the process of mixing the solid components and the solvent is also the process of slurry preparation and in-situ reaction. Here, in-situ reaction refers to the spontaneous chemical reaction that occurs on or near the surface of ammonium borate and sulfide solid electrolyte particles during the mixing process.

[0132] As an alternative example, mixing solid components and solvents includes: The solid components (the sulfide solid electrolyte powder, the binder, and the ammonium borate additive) and the solvent are placed in a mixing container and stirred, ball-milled, or high-speed sheared under an inert atmosphere (such as argon) or in a drying room (dew point ≤ -40°C) to form a uniform slurry.

[0133] In some embodiments, the film formation includes the following steps: S1. The slurry obtained by mixing is formed on a substrate to obtain a wet film; S2. Dry the wet film in an inert gas atmosphere or a vacuum environment.

[0134] For example, the method of forming the mixed slurry on the substrate in step S1 includes, but is not limited to, coating, impregnation, etc., and coating is optional. The coating method includes, but is not limited to, blade coating, casting, or spraying.

[0135] For example, the substrate in step S1 includes, but is not limited to, release film, metal foil, etc. The release film includes, but is not limited to, polyethylene terephthalate (PET) release film, polytetrafluoroethylene (PTFE) release film, polyimide (PI) release film, etc., and the metal foil includes, but is not limited to, aluminum foil, copper foil, carbon-coated aluminum foil, etc.

[0136] For example, the thickness of the wet film is 20-100µm, including but not limited to 25µm, 30µm, 40µm, 50µm, 60µm, 70µm, 80µm, 90µm or 95µm.

[0137] For example, in step S2, the inert gas includes at least one of helium, argon, and neon.

[0138] For example, in step S2, the drying temperature of 60-200℃ includes, but is not limited to, 70℃, 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, or 190℃; the drying time is 2-24 hours, including but not limited to 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, or 22 hours. In the embodiments of this application, the purpose of drying is to completely remove the solvent and form a self-supporting pre-formed film.

[0139] It should be noted that in step S2, the purpose of drying is to completely remove the solvent and form a self-supporting pre-formed film. Therefore, the film obtained after drying is the sulfide solid electrolyte membrane prepared by the method of this embodiment. This sulfide electrolyte membrane is transferred to the surface of the negative electrode sheet during battery assembly. Specifically, the negative electrode sheet includes a negative current collector, and at least one surface of the negative current collector is provided with a negative electrode material layer. The sulfide electrolyte membrane is transferred to the surface of the negative electrode material layer away from the negative current collector. Exemplarily, the negative electrode material layer includes a negative electrode active material, a negative electrode binder, a negative electrode conductive agent, a negative electrode thickener, etc. In the embodiments of this application, there are no restrictions on the selection of negative electrode current collector, negative electrode active material, negative electrode binder, negative electrode conductive agent, negative electrode thickener, etc., which can be any negative electrode current collector, negative electrode active material, negative electrode binder, negative electrode conductive agent, negative electrode thickener, etc., known in the art for use in battery, especially all-solid-state secondary battery negative electrode sheets, and their selection and dosage.

[0140] Optionally, the thickness of the sulfide solid electrolyte membrane is 20-100µm, including but not limited to 30µm, 40µm, 50µm, 60µm, 70µm, 80µm or 90µm.

[0141] The method for preparing the sulfide solid electrolyte membrane in this application embodiment can bring at least the following beneficial effects: (1) Excellent air stability: The prepared B and N co-doped sulfide solid electrolyte membrane exhibits a significant decrease in ionic conductivity after being exposed for the same period of time in a low dew point dry room (e.g., -20°C dew point). This greatly relaxes the requirements for the production environment.

[0142] (2) Maintaining high ionic conductivity: Due to the mild and uniform in-situ doping reaction, the main lithium-ion transport channels are not severely disrupted. The total ionic conductivity of the prepared sulfide solid electrolyte membrane can be maintained at room temperature. The apparent conductivity is comparable to that of undoped high-quality electrolytes, and some implementations even exhibit higher apparent conductivity due to interface optimization.

[0143] (3) Improve cycle life: The prepared sulfide solid electrolyte membrane can significantly improve the stability of the negative electrode interface, reduce side reactions and lithium dendrite growth, and achieve a longer cycle life.

[0144] (4) Technological and economic advantages: The preparation method is simple, does not require expensive equipment or extreme conditions, is highly compatible with existing battery slurry coating production lines, and the additive ammonium borate is inexpensive, making it highly promising for large-scale industrial application.

[0145] <Battery> The battery of this application embodiment includes a positive electrode, a negative electrode, and a solid electrolyte membrane. The solid electrolyte membrane includes the sulfide solid electrolyte membrane of this application embodiment, or the sulfide solid electrolyte membrane prepared by the preparation method of the sulfide solid electrolyte membrane of this application embodiment.

[0146] In some embodiments, the battery includes, or may be an all-solid-state battery.

[0147] In some embodiments, the battery includes a secondary battery, such as a lithium-ion battery or a sodium-ion battery, and may be a lithium-ion battery.

[0148] In some embodiments, the battery includes pouch cells.

[0149] As an optional example, the battery is an all-solid-state rechargeable battery, and more preferably an all-solid-state lithium-ion battery.

[0150] <Electrical Appliances> The electrical device in this application includes the battery in this application.

[0151] In some embodiments, the electrical device includes, but is not limited to, one of a vehicle, a lighting device, an electronic device, etc., and may be a vehicle, such as a car or a motorcycle.

[0152] The battery and the power device of this application embodiment both have at least the beneficial effects of the sulfide solid electrolyte membrane and the preparation method of the sulfide solid electrolyte membrane of this application embodiment.

[0153] The following non-limiting embodiments further illustrate certain features of the present technology.

[0154] I. Examples and Comparative Examples Example 1 This embodiment provides a sulfide solid electrolyte membrane, the preparation method of which includes the following steps: (1) Under the protection of an argon atmosphere, Solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate were mixed in xylene solvent at a mass ratio of 95:4:1 and stirred at 30°C to obtain a uniform slurry.

[0155] in, Solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium borate are the solid components; the mass content of the solid components is 50% based on the total mass of the solid components and solvents; the stirring speed is 250 rpm, and the stirring time is 3 hours.

[0156] (2) The slurry obtained in step (1) is coated onto a polyethylene terephthalate (PET) release film substrate by a scraping method to obtain a wet film.

[0157] (3) The wet film obtained in step (2) is dried in a vacuum environment to completely remove the solvent and form a self-supporting pre-made film, namely the sulfide solid electrolyte membrane of this embodiment.

[0158] The drying temperature was 120℃, and the drying time was 11 hours.

[0159] Example 2 This embodiment is basically the same as Embodiment 1, except that: In step (1), The mass ratio of solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate is 94:4:2.

[0160] Example 3 This embodiment is basically the same as Embodiment 1, except that: In step (1), The mass ratio of solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate is 93:4:3.

[0161] Example 4 This embodiment is basically the same as Embodiment 1, except that: In step (1), The mass ratio of solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate is 95.9:4:0.1.

[0162] Example 5 This embodiment is basically the same as Embodiment 1, except that: In step (1), The mass ratio of solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate is 91:4:5.

[0163] Example 6 This embodiment is basically the same as Embodiment 1, except that: In step (1), The mass ratio of solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate is 85:10:5.

[0164] Example 7 This embodiment is basically the same as Embodiment 1, except that: In step (1), The mass ratio of solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate is 99.4:0.5:0.1.

[0165] Example 8 This embodiment is basically the same as Embodiment 1, except that: In step (1), tetraboric acid is replaced with ammonium borate.

[0166] Example 9 This embodiment is basically the same as Embodiment 1, except that: In step (1), tetraboric acid is replaced with ammonium metaborate.

[0167] Example 10 This embodiment is basically the same as Embodiment 1, except that: In step (1), tetraboric acid is replaced with "a mixture of ammonium tetraborate and ammonium metaborate in a mass ratio of 1:1". Example 11 This embodiment is basically the same as Embodiment 1, except that: In step (1), Solid electrolyte powder replaced with Solid electrolyte powder, replacing hydrogenated nitrile butadiene rubber (HNBR) binder with polyvinylidene fluoride (PVDF) binder, and xylene solvent with butyl butyrate.

[0168] Example 12 This embodiment is basically the same as Embodiment 1, except that: In step (1), The solid electrolyte powder was replaced with Thio-LISICON type solid electrolyte powder, the hydrogenated nitrile butadiene rubber (HNBR) binder was replaced with styrene-butadiene rubber (SBR) binder, and the xylene solvent was replaced with anisole.

[0169] Example 13 This embodiment is basically the same as Embodiment 1, except that: In step (1), stirring is replaced by ball milling.

[0170] Example 14 This embodiment is basically the same as Embodiment 1, except that: In step (1), stirring is replaced by high-speed shearing at a speed of 50,000 rpm.

[0171] Example 15 This embodiment is basically the same as Embodiment 1, except that: In step (1), Solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate were mixed in xylene solvent at a mass ratio of 95:4:1 and stirred at 0°C to obtain a uniform slurry.

[0172] Example 16 This embodiment is basically the same as Embodiment 1, except that: In step (1), Solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate were mixed in xylene solvent at a mass ratio of 95:4:1 and stirred at 60°C to obtain a uniform slurry.

[0173] Example 17 This embodiment is basically the same as Embodiment 1, except that: In step (1), the mass content of the solid component is 10% based on the total mass of the solid component and the solvent.

[0174] Example 18 This embodiment is basically the same as Embodiment 1, except that: In step (1), the mass content of the solid component is 90% based on the total mass of the solid component and the solvent.

[0175] Example 19 This embodiment provides a sulfide solid electrolyte membrane, the preparation method of which includes the following steps: (1) In a dry room (dew point -40°C), Solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate were mixed in xylene solvent at a mass ratio of 95:4:1 and stirred at 30°C to obtain a uniform slurry.

[0176] in, Solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate are the solid components; the mass content of the solid components is 50% based on the total mass of the solid components and solvents; the stirring speed is 10 rpm, and the stirring time is 24 h.

[0177] (2) The slurry obtained in step (1) is coated onto an aluminum foil substrate by casting to obtain a wet film.

[0178] (3) The wet film obtained in step (2) is dried in an argon atmosphere to completely remove the solvent and form a self-supporting pre-made film, namely the sulfide solid electrolyte membrane of this embodiment.

[0179] The drying temperature was 60℃ and the drying time was 24 hours.

[0180] Example 20 This embodiment provides a sulfide solid electrolyte membrane, the preparation method of which includes the following steps: (1) In a dry room (dew point -40°C), Solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate were mixed in xylene solvent at a mass ratio of 95:4:1 and stirred at 30°C to obtain a uniform slurry.

[0181] in, Solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate are the solid components; the mass content of the solid components is 50% based on the total mass of the solid components and solvents; the stirring speed is 500 rpm and the stirring time is 10 min.

[0182] (2) The slurry obtained in step (1) is coated onto an aluminum foil substrate by casting to obtain a wet film.

[0183] (3) The wet film obtained in step (2) is dried in an argon atmosphere to completely remove the solvent and form a self-supporting pre-made film, namely the sulfide solid electrolyte membrane of this embodiment.

[0184] The drying temperature was 200℃ and the drying time was 2 hours.

[0185] Example 21 This embodiment is basically the same as Embodiment 1, except that: In step (1), The mass ratio of solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate is 90:4:6.

[0186] Comparative Example 1 This comparative example is basically the same as Example 1, except that: In step (1), The mass ratio of solid electrolyte powder, hydrogenated nitrile butadiene rubber (HNBR) binder, and ammonium tetraborate is 96:4:0. That is, the raw materials used in the preparation do not contain ammonium tetraborate.

[0187] Comparative Example 2 This comparative example is basically the same as Example 1, except that: Step (1) is as follows: Under the protection of an argon atmosphere, Solid electrolyte powder and ammonium tetraborate were mixed in xylene solvent at a mass ratio of 96:4 to obtain a uniform slurry.

[0188] II. Performance Testing 1. Electrolyte membrane characterization (1) Doping amounts of boron and nitrogen 1) The boron (B) doping content (wt%) in the electrolyte membrane (i.e., the sulfide solid electrolyte membrane or solid electrolyte membrane prepared in each embodiment or comparative example) was tested by inductively coupled plasma optical emission spectrometry (ICP-OES). The test results are shown in Table 1.

[0189] The specific testing method is as follows: Step 1: Accurately weigh 50 mg of electrolyte membrane sample and place it in a microwave digestion vessel lined with polytetrafluoroethylene; Step 2: Add 6 mL of commercially available concentrated nitric acid and 2 mL of 99 wt% hydrofluoric acid; seal the digestion vessel and place it in a microwave digester; then, digest according to a gradient temperature program. After the procedure is completed, cool to room temperature (25°C) to obtain the digestion solution; Step 3: Transfer all the digestion solution to a 50 mL polyethylene volumetric flask, dilute to the mark with ultrapure water, and shake well to obtain the mother liquor; take an appropriate amount of the mother liquor and dilute it 10 times with 2wt% dilute nitric acid to obtain the sample solution for testing. Step 4: Use an ICP-OES instrument to test the concentration of the sample solution, and calculate the boron doping content in the electrolyte membrane according to formula (1) based on the test results: Equation (1) In formula (1), C is the concentration of the sample solution measured by the instrument (mg / L), V is the volume of the mother liquor (50mL), D is the dilution factor (10 times), and m is the mass of the electrolyte membrane sample (50mg).

[0190] 2) The nitrogen (N) doping mass content (hereinafter referred to as nitrogen doping content (wt%)) in the electrolyte membrane (i.e., the sulfide solid electrolyte membrane or solid electrolyte membrane prepared in each embodiment or comparative example) was tested using an elemental analyzer. The test results are shown in Table 1.

[0191] The specific testing method is as follows: Step 1: Accurately weigh 5mg of electrolyte membrane sample and tightly wrap the sample with a solder ball; Step 2: Ensure that the elemental analyzer is powered on, the combustion furnace and reduction furnace have reached the set temperature (1150℃), the carrier gas (helium) and oxygen pressure are stable, and the baseline is flat. Step 3: Place the electrolyte membrane sample into the autosampler and start the test to obtain the nitrogen mass in the sample. Calculate the nitrogen doping content (wt%) in the electrolyte membrane according to formula (2) based on the test results: Equation (2) In formula (2), the mass of the electrolyte membrane sample is 5 mg.

[0192] 2. Ionic conductivity and ionic conductivity retention The test method for ionic conductivity and ionic conductivity retention includes the following steps: 1) Assemble the electrolyte membrane (i.e., the sulfide solid electrolyte membrane or solid electrolyte membrane prepared in each embodiment or comparative example) with two stainless steel sheets to form a stainless steel sheet symmetrical battery, and test the ionic conductivity of the electrolyte membrane at this time, which is recorded as σ1, with the unit being mS / cm.

[0193] 2) After exposing the electrolyte membrane (i.e. the sulfide solid electrolyte membrane or solid electrolyte membrane prepared in each embodiment or comparative example) to an environment with a dew point of -20°C for 24 hours, the exposed electrolyte membrane is then assembled with two stainless steel sheets to form a stainless steel sheet symmetrical battery (the stainless steel sheets used are the same as those used when testing σ1). The ionic conductivity of the electrolyte membrane after air exposure is tested and recorded as σ2, with the unit being mS / cm.

[0194] 3) The ionic conductivity retention rate of the electrolyte membrane after 24 hours of exposure at a dew point of -20°C was calculated using the formula for ionic conductivity retention rate.

[0195] The formula for calculating the retention rate of ionic conductivity is: .

[0196] The ionic conductivity and ionic conductivity retention are shown in Table 1.

[0197] 3. Electrochemical performance The electrolyte membranes prepared in each embodiment or comparative example (i.e., the sulfide solid electrolyte membranes or solid electrolyte membranes prepared in each embodiment or comparative example) were used to prepare all-solid-state lithium-ion secondary batteries, and the electrochemical performance of each prepared battery was tested. Wherein: The preparation method of an all-solid-state lithium-ion secondary battery includes the following steps: (1) Preparation of positive electrode: Weigh out the positive electrode in a mass ratio of 80:15:3:2 (i.e., NCM811) positive electrode active material, Solid electrolyte powder, HNBR binder, and vapor-grown carbon fiber (VGCF conductive carbon) are mixed evenly in xylene to obtain a positive electrode slurry with a solid content of 50%. The positive electrode slurry is coated on opposite sides of an aluminum foil with a thickness of 12 μm, and then dried and rolled to obtain a positive electrode sheet.

[0198] (2) Preparation of negative electrode sheet: Weigh out micron-sized silicon powder (average particle size 2μm) in a mass ratio of 80:15:3:2, negative electrode active material, Solid electrolyte powder, HNBR binder, and vapor-grown carbon fiber (VGCF conductive carbon) are mixed evenly in xylene to obtain a negative electrode slurry with a solid content of 50%. The negative electrode slurry is coated onto opposite surfaces of a 6μm thick copper foil, and after drying and rolling, a negative electrode sheet is obtained. The dried negative electrode slurry forms a negative electrode material layer.

[0199] (3) The above-mentioned positive electrode, negative electrode and electrolyte membrane (i.e. the sulfide solid electrolyte membrane or solid electrolyte membrane prepared in each embodiment or comparative example) are stacked, packaged and isostatically pressed to obtain an all-solid-state lithium-ion secondary battery. Among them, the sulfide electrolyte membrane is transferred to the surface of the negative electrode material layer away from the copper foil of the negative electrode current collector by transfer printing.

[0200] The electrochemical performance testing method is as follows: At 45°C, a constant pressure of 5 MPa was applied to the all-solid-state lithium-ion secondary battery. It was first charged at a constant current of 0.5C to 4.2V, then charged at a constant voltage until the current decayed to 0.05C, and finally discharged at a constant current of 0.5C to test the battery's cycle performance. The discharge capacity measured in the first cycle was recorded as 100%. The discharge capacity of the 500th cycle was divided by the discharge capacity measured in the first cycle, and this was recorded as the capacity retention rate after 500 cycles. The electrochemical performance test results are shown in Table 1 and Figure 1 As shown.

[0201] Table 1

[0202] As can be seen from Table 1, the sulfide solid electrolyte membranes prepared in each embodiment of this application have significantly improved ionic conductivity retention and 500-cycle capacity retention compared to the sulfide solid electrolyte membrane prepared in Comparative Example 1 without the addition of ammonium borate. This indicates that the sulfide solid electrolyte membranes prepared using the sulfide solid electrolyte membranes of this application have excellent air stability and electrochemical interface stability.

[0203] Furthermore, comparing Example 1 and Comparative Example 2, it can be seen that when the raw materials in the preparation method of the sulfide solid electrolyte of this application do not contain a binder, the sulfide solid electrolyte membrane prepared exhibits a significant decrease in both ionic conductivity retention and 500-cycle capacity retention, especially the 500-cycle capacity retention. This is because without a binder, processing and film formation are impossible.

[0204] also, Figure 1 The battery cycle curves are for an all-solid-state lithium-ion secondary battery containing the sulfide solid electrolyte membrane prepared in Example 2. Figure 1 It can be seen that the sulfide solid electrolyte membrane prepared using the method of this application has good electrochemical cycling stability.

[0205] In this application, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0206] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A sulfide solid electrolyte membrane, characterized in that, The sulfide solid electrolyte membrane is doped with boron and nitrogen.

2. The sulfide solid electrolyte membrane according to claim 1, characterized in that, The boron element in the sulfide solid electrolyte membrane has a mass content of 0.02-1%; And / or, the mass content of the N element in the sulfide solid electrolyte membrane is 0.002-0.4%.

3. The sulfide solid electrolyte membrane according to claim 1 or 2, characterized in that, The raw materials for preparing the sulfide solid electrolyte membrane include solid components and solvents. The solid components include sulfide solid electrolytes, additives, and binders. The additives include ammonium borate.

4. The sulfide solid electrolyte membrane according to claim 3, characterized in that, The ammonium borate includes at least one of ammonium tetraborate, ammonium metaborate, and ammonium orthoborate. And / or, the ammonium borate content in the solid component is 0.1-5% by mass; And / or, the sulfide solid electrolyte includes at least one of sulfide solid electrolyte of the silver-germanium sulfide type, LGPS type sulfide solid electrolyte, and thiolated LISICON type solid electrolyte; And / or, the sulfide solid electrolyte has a mass content of 85-99.4% in the solid component; And / or, the adhesive comprises at least one of styrene-butadiene rubber, polyvinylidene fluoride, polyurethane, nitrile rubber, hydrogenated nitrile rubber, and hydrogenated styrene-butadiene block copolymer; And / or, the binder has a mass content of 0.5-10% in the solid component; And / or, the solid component in the raw materials for preparation has a mass content of 10-90%; And / or, the solvent includes at least one of toluene, xylene, butyl butyrate, isobutyl isobutyrate, anisole, or hexane.

5. A method for preparing a sulfide solid electrolyte membrane, characterized in that, include: The solid components and solvent are mixed and formed into a film to obtain the sulfide solid electrolyte membrane; The solid component includes additives, including ammonium borate.

6. The preparation method according to claim 5, characterized in that, The ammonium borate includes at least one of ammonium tetraborate, ammonium metaborate, and ammonium orthoborate. And / or, the ammonium borate content in the solid component is 0.1-5% by mass; And / or, based on the total mass of the solid component and the solvent, the mass content of the solid component is 10-90%; And / or, the solid component further includes a sulfide solid electrolyte and a binder; And / or, the solvent includes at least one of toluene, xylene, butyl butyrate, isobutyl isobutyrate, anisole, or hexane.

7. The preparation method according to claim 6, characterized in that, The sulfide solid electrolyte includes at least one of the following: silver sulfide-germanium sulfide solid electrolyte, LGPS-type sulfide solid electrolyte, and thiolated LISICON-type solid electrolyte. And / or, the sulfide solid electrolyte has a mass content of 85-99.4% in the solid component; And / or, the adhesive comprises at least one of styrene-butadiene rubber, polyvinylidene fluoride, polyurethane, nitrile rubber, hydrogenated nitrile rubber, and hydrogenated styrene-butadiene block copolymer; And / or, the binder has a mass content of 0.5-10% in the solid component.

8. The preparation method according to any one of claims 5 to 7, characterized in that, The mixing is carried out in an inert gas atmosphere or in a drying room; And / or, the mixing method includes at least one of stirring, ball milling, and high-speed shearing; the high-speed shearing speed is 1000-100000 rpm; And / or, the mixing temperature is 0-60°C, and the mixing time is 10 min to 24 h; And / or, the film formation includes: The slurry obtained by mixing is formed on a substrate to obtain a wet film; The wet film is dried in an inert gas atmosphere or a vacuum environment.

9. A battery comprising a positive electrode, a negative electrode, and a solid electrolyte membrane, characterized in that, The solid electrolyte membrane includes the sulfide solid electrolyte membrane as described in any one of claims 1 to 4, or the sulfide solid electrolyte membrane prepared by the preparation method as described in any one of claims 5 to 8.

10. An electrical device, characterized in that, Includes the battery as described in claim 9.

11. The electrical appliance according to claim 10, characterized in that, The electrical device includes one of the following: a vehicle, a lighting device, or an electronic device.